Descriptions of Thereza murutinga sp. nov. and Pristocnemis caipira sp. nov., and new records of Caelopyginae (Opiliones: Laniatores: Gonyleptidae) - Dasilva, Marcio Bernardino; Pinto-Da-Rocha, Ricardo (Zootaxa, 2012)
Two new species of Caelopyginae are described: Pristocnemis caipira sp. nov. from Parque Nacional da Serra da Canastra,Minas Gerais, Brazil, and Thereza murutinga sp. nov., from Parati, Rio de Janeiro, Brazil. Pristocnemis caipira sp. nov. isdiagnosed by shallow grooves on the dorsal scutum, a lower number of tarsal segments, presence of a spine on the anal opercu-lum, large, pointed tubercles on the lateral margins of the dorsal scutum, and an absence of white patches on the dorsal scutum.Thereza murutinga sp. nov. is diagnosed by the combination of the following characters: incomplete median longitudinalgroove on area III and absent on area II, prosoma much smaller than opisthosoma, and a large white patch covering theprosoma and whole areas of the opisthosomal scutum. A cladistic analysis including the two new species was performed toinvestigate their relationship within the subfamily. We obtained 927 trees of 185 steps (CI=0.4, RI=0.74), which corroboratedthe generic assignments of the new species, but infrageneric relationships remained unsolved. In addition, male genitalia ofAmpheres luteus (Giltay) and genera Pristocnemis and Thereza are redescribed, new distribution records for Caelopyginae species are presented, and biogeographical implications are discussed.